ANALISIS PENGARUH MODAL KERJA DAN JAM KERJA TERHADAP PENDAPATAN BERSIH PEDAGANG KAKI LIMA DI PASAR GOTONG ROYONG BATUMARTA 2 - Sally Maria Bramana; Rini Apriyani (STIE DWI SAKTI BATURAJA, 2019)
The purpose of this study was to find out how the influence of working capital and working hours on net income. Based on the results of research and discussion conducted, it can be concluded that the results of multiple linear regression analysis are obtained as follows: Y = 49,810 + 0,170 X1 + 6,090 X2 + e. Correlation value (R) between variables of working capital, working hours, and net income of 0.564. This shows that the relationship between working capital, working hours and net income has a sufficient relationship. The coefficient of determination (R square) that is equal to 0.319 or 31.9%, this shows that the variation in changes in the variable net income (Y) is influenced by the dependent variable namely working capital (X1) and working hours (X2) of 31.9%. While the remaining 68.1% is influenced by other factors outside of this study. Based on t test, working capital (X₁) t-count (4,006)> t-table (2,009) then Ho is accepted and Ha is accepted, meaning that there is an effect of working capital on the net income of street vendors in Gotong Royong Batumarta Market 2. Working hours ( X₂) t-count (1,360) <t-table (2,009) then Ho is accepted and Ha is rejected, meaning that there is no influence of working hours on the net income of street vendors in Gotong Royong Batumarta Market 2. Based on F test, F-count (11,685 )> F-table (3,183) then Ho is rejected and Ha is accepted, meaning that there is the influence of working capital and working hours on the net income of street vendors in the Gotong Royong Batumarta Market 2.